Heart Rate Variability Findings as a Predictor of Atrial Fibrillation in Middle‐Aged Population. (9th April 2014) - PERKIÖMÄKI, JUHA; UKKOLA, OLAVI; KIVINIEMI, ANTTI; TULPPO, MIKKO; YLITALO, ANTTI; KESÄNIEMI, Y. ANTERO; HUIKURI, HEIKKI
Heart Rate Variability and Atrial Fibrillation Background Autonomic nervous system modifies atrial electrophysiologic properties and arrhythmia vulnerability. Methods Heart rate (HR) variability, an indicator of cardiac autonomic regulation, was measured in 784 subjects (mean age 51 ± 6 years; 54% males) from a standardized 45‐minute period in a study population (n = 1, 045), which consisted of randomly selected hypertensive and age‐ and sex‐matched control subjects at the time of recruitment in 1991–1992 (the OPERA study). Results During a mean follow‐up of 16.5 ± 3.5 years, 76 subjects (9.7%) had developed symptomatic atrial fibrillation (AF), needing hospitalization. HR did not predict the occurrence of AF. Among the various spectral and time‐domain HR variability indexes, only the low‐frequency (LF) spectral component independently predicted AF. In the Cox regression analysis, the hazard ratio of reduced HR corrected LF (LFccv ≤ 1.59%, optimal cutoff from the ROC curve) in predicting the AF was 3.28 (95% CI: 2.06–5.24; P < 0.001). In the multiple Cox regression model, including LFccv and other predictors of AF, such as age, gender, hypertension, history of coronary artery disease, systolic and diastolic blood pressure, body mass index, β‐blocking, angiotensin converting enzyme inhibitor and aspirin medication, left atrial size, left ventricular mass index, and left ventricular size obtained by echocardiography, only LFccv (hazard ratio 2.81; 95% CI: 1.64–4.81; P < 0.001), age (P = 0.006), and systolic blood pressure (P = 0.02) remained as significant predictors of AF. Conclusions Impaired LF oscillation of HR predicts new‐onset AF in a middle‐aged population emphasizing the important role of autonomic nervous system in the genesis of symptomatic AF.